Social factors associated with trust in the health system in northern Sweden: a cross-sectional study - Mazen Baroudi; Isabel Goicolea; Anna-Karin Hurtig; Miguel San-Sebastian (BMC, 2022)
Abstract Background Despite the importance of having trust in the health system, there is a paucity of research in this field in Sweden. The aim of this study was to estimate the level of trust in the health system and to assess the factors associated with it in northern Sweden. Methods A cross-sectional survey was conducted in 2014 in the four northern regions of Sweden. A total of 24 795 participants (48% response rate) aged 18 to 84 years were involved in the study. A log-binomial regression was used to measure the association between sociodemographic factors and trust in the health system. Results Two thirds of the participants (68.5%) reported high trust in the health system i.e. had very much or quite a lot confidence in the health system. Women had lower prevalence of trust compared to men (PR = 0.96; 95% CI = 0.94-0.98) while older participants had a higher trust compared to youth (PR = 1.11; 95% CI = 1.06-1.16). Participants with lower level of education, those who experienced economic stress, those who were born outside Sweden and those living in small municipalities also had lower prevalence of trust in the health system. Conversely, lower income was associated with higher trust (PR = 1.08; 95% CI = 1.04-1.12). Finally, a strong relationship between higher social capital (having emotional and instrumental support, horizontal trust, and higher social participation) and trust in the health system was also found. Conclusions Trust in the health system was moderately high in northern Sweden and strongly associated with sociodemographic and social capital factors. Trust is a complex phenomenon and a deeper exploration of the relation between trust in the health system and sociodemographic factors is needed.